A Bibliometric Study on Digital Entrepreneurship: Mapping the Evolutions and Its Impact on Startups - Judijanto, Loso; Arfiansyah, Ferry (Westscience Press, 2024)
This study presents a bibliometric analysis of digital entrepreneurship, mapping its evolution, key themes, and impact on startups. Utilizing data from peer-reviewed publications from 2005 to 2025, the research highlights a significant surge in scholarly interest, particularly post-2015, driven by advancements in digital technologies and their implications for entrepreneurship. The analysis identifies central themes such as